Influence and the role of sports in human life (Eurasian Journal of Humanities and Social Sciences, 2022)
Sports are an independent type of human activity, which plays an important role in the development of society. They have a vital impact on social production, the development of social relations, the formation of a person as a person. In this article, the author describes in detail the role of sports in public life.